2006
DOI: 10.1261/rna.26506
|View full text |Cite
|
Sign up to set email alerts
|

U1-like snRNAs lacking complementarity to canonical 5′ splice sites

Abstract: We have detected a surprising heterogeneity among human spliceosomal U1 small nuclear RNA (snRNA). Most interestingly, we have identified three U1 snRNA variants that lack complementarity to the canonical 59 splice site (59SS) GU dinucleotide. Furthermore, we have observed heterogeneity among the identified variant U1 snRNA genes caused by single nucleotide polymorphism (SNP). The identified snRNAs were ubiquitously expressed in a variety of human tissues representing different stages of development and displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 54 publications
4
38
0
Order By: Relevance
“…We have focused our attention on the entire U1 snRNA class I pseudogene locus and shown that 50% of the vU1 snRNA genes annotated within this 6.8-Mb region express an snRNA in HeLa cells and that all 21 vU1 snRNA genes are active, at varying levels, in hESCs. In addition, three other vU1 snRNAs (U1A5, U1A6, and U1A7) were also previously isolated from HeLa cells (Kyriakopoulou et al 2006). A ''BLAT'' search of their sequences indicates that they map to different locations on the human genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have focused our attention on the entire U1 snRNA class I pseudogene locus and shown that 50% of the vU1 snRNA genes annotated within this 6.8-Mb region express an snRNA in HeLa cells and that all 21 vU1 snRNA genes are active, at varying levels, in hESCs. In addition, three other vU1 snRNAs (U1A5, U1A6, and U1A7) were also previously isolated from HeLa cells (Kyriakopoulou et al 2006). A ''BLAT'' search of their sequences indicates that they map to different locations on the human genome.…”
Section: Discussionmentioning
confidence: 99%
“…Since the U1 snRNA is not translated into a protein, active pseudogenes could generate variant functional snRNAs. It has been known for some time that minor U1-like snRNAs, with variation to the human U1 snRNA exist, but to date, their function remains elusive (Patton and Wieben 1987;Lund 1988;Kyriakopoulou et al 2006). We questioned whether variant U1 snRNAs, encoded by class I pseudogenes, could play a role in regulating gene expression in vivo.…”
mentioning
confidence: 96%
“…Finally, we used U1-specific RNA decoys (Roca and Krainer 2009) to confirm that all of the tested 59ss in the SMN1/2 contexts are indeed recognized by U1 and not by other U1-like snRNAs (Kyriakopoulou et al 2006). These vector-driven RNA decoys sequester endogenous U1, resulting in the loss of 59ss recognition and, consequently, in SMN1/2 exon 7 skipping.…”
Section: Registers With Bulges At the 59 End Of U1mentioning
confidence: 97%
“…Distinguishable snRNA paralogs that are often differentially expressed have previously been reported for a diverse collection of major spliceosmal snRNAs including U1 snRNAs in insects [43,64,77], Xenopus [12], and human [39], U2 snRNAs in Dictyostelium [29], sea urchin [80] and silk moth [77], U5 snRNAs in human [79], sea urchin [52], and Drosophilids [8], U6 snRNAs in silk moth [78] and human [85,14].…”
Section: Phylogenetic Analysis and Paralogsmentioning
confidence: 99%
“…Very recently, however, some of these variants have been studied in more details, see e.g. [64,8,39,77,29,78] and the references therein. The only systematic study that we are aware of is the recent comprehensive analysis of 11 insect genomes [53] which reported that phylogenetic gene trees of insect snRNAs do not provide clear support for discernible paralog groups of U1 and/or U5 snRNAs that would correspond to the variants with tissue-specific expression patterns.…”
Section: Introductionmentioning
confidence: 99%